Low platelet monoamine oxidase activity in headache: no correlation with phenolsulphotransferase, succinate dehydrogenase, platelet preparation method or smoking. - Littlewood, J (1984)
Platelet monoamine oxidase activity in male migrainous and cluster headache patients was significantly lower than in male controls, confirming our previous study. The activity range showed a normal distribution and low mean values could not be attributed to a subgroup with particularly low activity. When Corash 's platelet preparation method was used, with its high platelet yield, specific enzyme activities of a similar order were obtained. Thus, the low values encountered were not due to abnormal recovery within the platelet population. Two other enzyme activities, phenolsulphotransferase M and succinate dehydrogenase, were also measured in the same platelet samples. Although low succinate dehydrogenase activity was identified in the headache groups, it appeared to represent a separate phenomenon and there was no significant correlation between activity of either enzyme and that of monoamine oxidase. This shows that the low activity of platelet monoamine oxidase in headache is not related to a generalised platelet enzyme deficit. It was also shown that the low monoamine oxidase activity in the headache patients could not be attributed to smoking.